Non-Operative Management of Hip Osteoarthritis - Marks, Ray (Scientific Research, 2015)
This paper reviews several non-operative and non-pharmacologic management strategies advocated for alleviating the pain and disability experienced by people with hip osteoarthritis. It analyzes whether painful debilitating hip osteoarthritis, which has no effective cure and is often progressive, may be affected positively by non-operative interventions designed to control osteoarthritis pain. Finally, it provides an integrated plan of management for ameliorating hip osteoarthritis pain and disability in light of this knowledge.
Keywords: Hip Osteoarthritis; Intervention; Pain; Rehabilitation; Treatment